Partisipasi Anggaran Terhadap Kinerja Manajerial Dengan Pelimpahan Wewenang Sebagai Variabel Moderating - Aderina K Harahap; Hon Husni (Universitas Malahayati, 2017)
This research is done to find out the roles of corporate actors in budgetary participation asexpected as corporate goals. The budget participation is needed by delegation of authority to givechance to staffs to be participated in the process of budget preparation.It is therefore necessary to analyze the effect of budgetary participation on managerial performanceand delegation of authority in moderating the effect of budgetary participation on managerialperformance.The populations that are in charge in this study were 52 staffs who are participated in theimplementation of the budgetary participation and they were stated as research sample. The methodthat used was interview using questionnaire method then it was analyzed by using doubled linearregression.